New binders for Li-ion batteries - Peck, Steve Teck Wei (2019)
Silicon, as a potential lithium ion battery anode material, possesses extremely high specific capacity and low potential with respect to lithium metal resulting in high specific energy. However, silicon anodes tend to have poor cycle life due to large volumetric changes that occur during charging and discharging. As a result, the selection of binders that enhance adhesion within the anode becomes extremely significant in the case of silicon. Herein, a comparison between conventional PVDF binder and new pectin binder was made in terms of cycling performance and rate capability. Since a silicon and graphene composite with carbon black and the chosen binder were used to synthesise the electrode slurry, the optimum silicon to graphene weight ratio for electrodes with the new pectin binder was also investigated. Half-cells with lithium foil as the reference electrode were fabricated from a silicon-graphene composite electrode slurry with either PVDF or pectin binder using typical coin cell fabrication techniques and tested extensively using the Neware Battery Testing System (BTS).The feasibility of pectin binder as a potential attractive anode binder alternative was subsequently assessed. Cyclic voltammetry (CV) profiles and galvanostatic charge-discharge profiles for the different sets of electrodes were subsequently compared. Results obtained from these tests show great similarity to those obtained in literature, indicating the occurrence of identical electrochemical reactions. Cycling performance tests and rate capability tests were also conducted to compare the different sets of electrodes. It was found that pectin binder was superior to conventional PVDF binder in both cycling performance and rate capability, consistent with observations of micrographs obtained from Scanning Electron Microscopy (SEM) imaging. Varying the silicon loading in the electrode produced results that were consistent with the theory described in the literature review, with initial capacity increasing and capacity retention decreasing with increased silicon loading. The optimum silicon loading for the synthesised electrode with the pectin binder used in this project is proposed to exist somewhere between 1:3 and 1:1 weight ratio. The results obtained are a proof of concept of the attractiveness of the use of pectin as a new binder to obtain enhanced battery properties which could enable lithium-ion batteries to meet increasingly harsh demands in applications such as electric vehicles (EVs) and portable electronics.